2006
DOI: 10.1007/s00421-006-0189-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal power-to-mass ratios when predicting flat and hill-climbing time-trial cycling

Abstract: The purpose of this article was to establish whether previously reported oxygen-to-mass ratios, used to predict flat and hill-climbing cycling performance, extend to similar power-to-mass ratios incorporating other, often quick and convenient measures of power output recorded in the laboratory [maximum aerobic power (W MAP ), power output at ventilatory threshold (W VT ) and average power output (W AVG ) maintained during a 1 h performance test]. A proportional allometric model was used to predict the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
(47 reference statements)
4
18
0
Order By: Relevance
“…The tests performed in descent (coasting-down method) measure the acceleration of the cyclist in free-wheel and those performed on flat terrain (outdoor and indoor) measure the cyclist's deceleration, also in free-wheel. In a specified position i) in a descent (Gross et al, 1983;Kyle & Burke, 1984;Nevill et al, 2006) or ii) on flat ground, in a field, or in hallways (Candau et al, 1999) the cyclists brought the bicycle to a defined velocity before they stopped pedalling. The riding position was unchanged and, to reproduce actual conditions with turbulence induced by movement of the lower limbs, the cyclists can pedal without transmission of force to the rear wheel during coasting trials (Gross et al, 1983;Kyle & Burke, 1984;Candau et al, 1999).…”
Section: The Coasting-down and Deceleration Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The tests performed in descent (coasting-down method) measure the acceleration of the cyclist in free-wheel and those performed on flat terrain (outdoor and indoor) measure the cyclist's deceleration, also in free-wheel. In a specified position i) in a descent (Gross et al, 1983;Kyle & Burke, 1984;Nevill et al, 2006) or ii) on flat ground, in a field, or in hallways (Candau et al, 1999) the cyclists brought the bicycle to a defined velocity before they stopped pedalling. The riding position was unchanged and, to reproduce actual conditions with turbulence induced by movement of the lower limbs, the cyclists can pedal without transmission of force to the rear wheel during coasting trials (Gross et al, 1983;Kyle & Burke, 1984;Candau et al, 1999).…”
Section: The Coasting-down and Deceleration Methodsmentioning
confidence: 98%
“…Many authors have established a mathematical cycling model (e.g. Atkinson et al, 2007;Broker et al, 1999;di Prampero et al, 1979;Heil et al, 2001;Martin et al, 2006;Nevill et al, 2006;Olds, 1998Olds, , 2001Olds et al, 1993Olds et al, , 1995Padilla et al, 2000), most including terms for power output produced by the cyclist and power required to overcome aerodynamic drag, rolling resistance, and other parameters (Martin et al, 2006). At displacement velocity greater than 14 m/s where the aerodynamic drag is about 90% of the total resistive forces, according to Equations 1 and 2, it can be assumed that the mechanical power output is proportional to the product of aerodynamic drag and velocity.…”
Section: How To Minimise Aerodynamic Dragmentioning
confidence: 99%
“…As 2000 m rowing speed increases in proportion to the rate of energy expended by the rower but will also be limited by the drag/resistance of the ergometer, our initial model to explain 2000 m rowing ergometer speed was based on the following proportional (curvilinear) allometric or power‐function models (Nevill et al, 2006; Ingham et al, 2008), where is the power at V̇O 2max , “ a ” is a constant and “ k 1 ” is the exponents likely to provide the best predictor of rowing speed, and “ɛ” is the multiplicative error ratio.…”
Section: Methodsmentioning
confidence: 99%
“…This is accentuated particularly when the athletes are exercising against gravity by lifting their body mass in uphill slopes. A previous study, with the corresponding scaling allometric approach, showed that uphill cycling was associated with a higher body mass scaling factor for maximal oxygen consumption than for level-ground cycling (Nevill et al, 2006). In contrast, when performance in middle-distance running was modelled, the body mass of the athletes did not make a contribution to the proportional allometric model (Ingham et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…A different allometric scaling approach is applied when evaluating the performance capacity of athletes. This scaling approach has been used to evaluate the performance of endurance athletes in cycling (Jobson, Woodside, Passfield, & Nevill, 2008;Nevill, Jobson, Davison, & Jeukendrup, 2006;Nevill, Jobson, Palmer, & Olds, 2005), running (Ingham et al, 2008;Nevill, Ramsbottom, & Williams, 1992), and rowing (Nevill, Allen, & Ingham, 2011;Nevill, Beech, Holder, & Wyon, 2010).…”
Section: Introductionmentioning
confidence: 99%